Excellent Lubricity of PVA/PEG/CS Composite on Ceramic Surface and Stainless Steel Friction Pair. Issue 14 (29th May 2022) - Liu, Tao; Lu, Hailin; Wei, Qianyang; Li, Chengzhi; Chen, Lu; Feng, Ziqin; Tu, Nan
Abstract : At present, polymers such as polyethylene glycol (PEG) and chitosan (CS) are widely studied because of their excellent lubricating properties. Herein, powder combinations of different mass ratios are obtained by changing the mass of CS, and polymer films are obtained by hot pressing on the surface of the aluminum disk after microarc oxidation (MAO). The structure and crystallinity of the polymer composite film are characterized by X‐ray diffraction (XRD), Fourier‐transform infrared (FTIR), and X‐ray photoelectron spectroscopy (XPS), which show that there is no chemical reaction between various substances. The tribological properties of the composite film are evaluated. Experiments show that when the mass ratio of polyvinyl alcohol (PVA), PEG, and CS is 5:5:1.5, the composite film has excellent lubrication performance, and the friction coefficient reaches 0.068 under long‐time running in. This effect meets the social requirements for lubrication performance to a certain extent and is expected to replace some mature solid lubricants. Abstract : When the mass ratio of PVA: PEG: CS is 5:5:1.5, the friction coefficient reaches 0.068 under long‐time running through the effect of hydrogen bond. Compared with the working condition without composite film, the lubrication performance is improved by ten times. The results show that the lubrication performance is excellent.